Modernization and Innovation Development of Industrial Systems through Raising Private Capital - O. N. Kalinina (Вестник Российского экономического университета имени Г. В. Плеханова, 2019)
The quality of project documents, in particular, pricing and estimate standardization used in them can impact indicators of project efficiency and control over quality management of their implementation. The article analyzes principle challenges of the innovation development of production systems. The author worked out the method of fixed capital shaping based on higher accuracy of identifying sizes of investment at all stages of the investment cycle through better quality of project and estimate documents. A method of finding the value of projects was put forward, whose essence lies in using the information theory of project evaluation at all stages of projecting by indicators of its information difficulty. The sequence of stages in project implementation was substantiated by splitting-up jobs of preparatory and main period. Thus the value of the project is identified not by constructive parameters, but by the general value of parametric difficulty. As a result of the analysis the author came to the following conclusion: the use of the method of estimating project component value gives an opportunity to coordinate the technical level of the project, while its parameters are brought in conformity with the 6-th technological structure.